1995
DOI: 10.1084/jem.181.2.475
|View full text |Cite
|
Sign up to set email alerts
|

The development of T and non-T cell lineages from CD34+ human thymic precursors can be traced by the differential expression of CD44.

Abstract: SummaryIn addition to T-lineage cells, a small proportion of hematopoietic non-T cells are present in the human postnatal thymus. However, the origin of this minor non-T cell thymic compartment is presently unknown. In this study we have analyzed the developmental potential of the earliest human intrathymic precursors, characterized as CD34 § cells expressing intermediate levels of CD44. We show that these CD34 § CD44 jut thymocytes cultured with interleukin 7 were able to develop simultaneously into both T-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 35 publications
3
60
0
2
Order By: Relevance
“…24,43 Finally, addition of IL-7 to fetal thymic organ cultures led to DC development. 47 In our study, we report now in vivo evidence supporting such a role in DC development. While some of the effects we observed on steady-state numbers of cDCs and pDCs may be indirect, we obtained genetic evidence for a cell-intrinsic role of IL-7R in their development.…”
mentioning
confidence: 69%
“…24,43 Finally, addition of IL-7 to fetal thymic organ cultures led to DC development. 47 In our study, we report now in vivo evidence supporting such a role in DC development. While some of the effects we observed on steady-state numbers of cDCs and pDCs may be indirect, we obtained genetic evidence for a cell-intrinsic role of IL-7R in their development.…”
mentioning
confidence: 69%
“…10,11,33,34 However, those progenitors express CD34, which is not the case for leukemic pDCs. The capacity of the malignant cells to differentiate into T, B, or NK cells has to be tested, but at present we have shown that they are not precursors of monocytes or macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, after comparison of their phenotype with that of all known hematopoietic cells, we postulated that these cells are related to the newly characterized plasmacytoid dendritic cell (pDC). 8 The pDCs are members of the heterogeneous dendritic cell family that could be derived from human bone marrow 9 and thymus 10,11 lymphoid-restricted progenitors. They have been identified in peripheral blood [12][13][14] and in T-cell areas of tonsils, 8 lymph nodes, 15 and thymus.…”
Section: Introductionmentioning
confidence: 99%
“…IL-7 also influences the development and function of dendritic cell populations and mobilizes myeloid populations. 145 Indeed, IL-7 treatment of TN thymocytes induces the development of thymic dendritic cells (DCs) 146 and thymic macrophages, 147 and when IL-7 production is inhibited, the generation of thymic DCs is substantially reduced, suggesting that physiologic levels of IL-7 are important in the development of thymic DCs. 148 Similarly, in mice, IL-7-containing cocktails are capable of generating thymic DCs from early thymic progenitors, and the use of IL-7 in such cultures precludes the requirement for GM-CSF.…”
Section: Il-7 and Dendritic Cellsmentioning
confidence: 99%